Laws of Ecology and Their Promise of Explanations - Viorel Pâslaru (Philosophy, Theory, and Practice in Biology, 2022)
A number of ecologists have put forward various proposals that ecology has laws, yet they have not explicated what role laws play in ecological explanations. Marcel Weber (1999), Lev Ginzburg and Mark Colyvan (2004) correct this deficiency and also make their case for laws of ecology: the principle of competitive exclusion and Malthus's law of exponential growth respectively. According to Weber, the principle of competitive exclusion explains phenomena (1) by direct application, or (2) by describing a default state from which observed phenomena deviate and mechanisms are called to account for the discrepancy. Independently of Weber, Ginzburg and Colyvan articulate a role similar to (2) for Malthus's law. I argue that Weber's proposition of explanation by direct application is not consistent with Gause's account of "bottle experiments" that he uses to support it and does not do justice to ecologists' explanatory practice. To address these problems, I articulate an alternative account of explanation by direct application—the covering-law model—based on a proposal by Elgin and Sober (2002) and show that even in this proposal mechanisms play a key explanatory role. I also demonstrate how the covering-law model accounts for how Malthus's law can explain by direct application and for its role of descriptor of a default state. Finally, I argue that the views on laws as components in covering-law model explanations or as descriptors of default states do not give sufficient attention to the prominent explanatory role of mechanisms and to the demanding task of identifying and describing them, and ought to be corrected.